2020
DOI: 10.7556/jaoa.2020.133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Spin” in the Abstracts of Randomized Controlled Trial Reports in Cardiology

Abstract: Context The misrepresentation and distortion of research findings, known as “spin,” has been shown to affect clinical decision making. Spin has been found in randomized controlled trials (RCTs) published in various fields of medicine. Objective To evaluate the abstracts of RCTs found in the cardiology literature for spin. Methods The authors searched PubMed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…26 Another study identified spin in 34.5% of abstracts of systematic reviews and meta-analyses in emergency medicine. 27 Similarly, Roberts et al 28 evaluated spin in abstracts of cardiology trials and found evidence of spin in 27.3% of trial abstracts. 28 There were lower rates of consistent reporting among other trial characteristics between conference and publication abstracts, including sample sizes, follow-up periods and effect size estimates, which does not rule out the possibility of misreporting at conferences and/or their subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Another study identified spin in 34.5% of abstracts of systematic reviews and meta-analyses in emergency medicine. 27 Similarly, Roberts et al 28 evaluated spin in abstracts of cardiology trials and found evidence of spin in 27.3% of trial abstracts. 28 There were lower rates of consistent reporting among other trial characteristics between conference and publication abstracts, including sample sizes, follow-up periods and effect size estimates, which does not rule out the possibility of misreporting at conferences and/or their subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similarly, Roberts et al 28 evaluated spin in abstracts of cardiology trials and found evidence of spin in 27.3% of trial abstracts. 28 There were lower rates of consistent reporting among other trial characteristics between conference and publication abstracts, including sample sizes, follow-up periods and effect size estimates, which does not rule out the possibility of misreporting at conferences and/or their subsequent publications. For instance, for sample size, safety endpoint and effect size reporting consistency, we found rates that ranged between 50% and 75%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, discrepancies have been found between specialties. For example, 70% of otolaryngology abstracts contain spin in comparison to 44.3% of emergency medicine abstracts, and 27.3% of cardiology abstracts [ 9 11 ]. Due to the variability in results of past research, further exploration is warranted to examine the presence of spin in additional fields.…”
Section: Introductionmentioning
confidence: 99%